Self-medication in adults attending the drugstores of Distrito Jesús Nazareno, Ayacucho 2015 - Pillaca Medina, Mery Luz (2016)
Introduction. Self-medication is a serious problem that affects population health. Studies show that there is relation between selfmedication and sociodemographic and cultural factors. Objective. To determine the frequency and characteristics of self-medication in adults who go to the pharmacies. Design. Descriptive cross-sectional study. Setting. Jesus Nazareno District (JND), Ayacucho, Peru. Interventions. Prior informed consent surveys were conducted on adults who attended 22 drugstores from September to December 2015. The sample was a simple probabilistic random one, formed by 433 people 25 to 65 years old. The survey was approved by the Institutional Research Ethics Committee of the Peruvian National Institute of Health. Data were processed with the statistical program SPSS 19.0. Results. The frequency of self-medication was 87.8%. Women (67.9%) self-medicated more than men, both had higher education (42.9%). The main health problem was pain (64.7%) and respondents felt that their disease was mild (92.1%) and they had to wait too long in health services (18.7%). 69.4% of people had received advice from a health technician, and 74.7% had been influenced by television. Respondents mainly consumed analgesics (64.7%). Conclusions. The frequency of self-medication in adults from JND was high; it presented in eight out of ten people with higher education, and females predominated. The main health problem was pain. The type of drug most commonly used were painkillers, mainly because people felt that their illness was mild, and considered the waiting time in health services was too long.